Exposome and foetoplacental vascular dysfunction in gestational diabetes mellitus. (October 2022) - Valero, Paola; Fuentes, Gonzalo; Cornejo, Marcelo; Vega, Sofía; Grismaldo, Adriana; Pardo, Fabián; García-Rivas, Gerardo; Hillebrands, Jan-Luuk; Faas, Marijke M.; Casanello, Paola; van der Beek, Eline M.; van Goor, Harry; et al.
Abstract: A balanced communication between the mother, placenta and foetus is crucial to reach a successful pregnancy. Several windows of exposure to environmental toxins are present during pregnancy. When the women metabolic status is affected by a disease or environmental toxin, the foetus is impacted and may result in altered development and growth. Gestational diabetes mellitus (GDM) is a disease of pregnancy characterised by abnormal glucose metabolism affecting the mother and foetus. This disease of pregnancy associates with postnatal consequences for the child and the mother. The whole endogenous and exogenous environmental factors is defined as the exposome. Endogenous insults conform to the endo -exposome, and disruptors contained in the immediate environment are the ecto -exposome. Some components of the endo -exposome, such as Selenium, vitamins D and B12, adenosine, and a high-fat diet, and ecto -exposome, such as the heavy metals Arsenic, Mercury, Lead and Copper, and per- and polyfluoroakyl substances, result in adverse pregnancies, including an elevated risk of GDM or gestational diabesity. The impact of the exposome on the human placenta's vascular physiology and function in GDM and gestational diabesity is reviewed.